AtlasSQL-BR: A Brazilian Portuguese Geospatial Text-to-SQL Dataset with Spatial Hierarchies - O. Lopes, Diego; Braghetto, Kelly R. (Anais do Simpósio Brasileiro de Banco de Dados (SBBD); 2026: Anais do XLI Simpósio Brasileiro de Bancos de DadosDO - 10.5753/sbbd.2026.249149, 2026)
The Text-to-SQL task, which translates natural language into SQL queries, democratizes database access by enabling non-experts to query and analyze data effectively. While the field has seen significant progress, state-of-the-art models still fall short in processing geospatial queries due to a lack of diverse spatial data in existing training sets. This issue is compounded by the overwhelming dominance of English-language resources, leaving languages like Brazilian Portuguese largely underexplored. To bridge these gaps, we introduce AtlasSQL-BR, a novel, real-world geospatial Text-to-SQL dataset in Brazilian Portuguese. Built upon school census data and geographic boundary hierarchies, this dataset provides a robust benchmark for geospatial queries.